(untitled) (Nonconventional Technologies Review, 2023)
This research paper looks at the surface quality acquired during the laser cutting of metallic materials, with an emphasis on S235JR. We conducted studies on a FiberMak Momentum Gen-2 laser cutting machine to determine the effect of process settings on surface quality. We varied laser beam power and feed rate while keeping other parameters constant, such as nozzle diameter, CO2 pressure, and focal length. Results showed that surface quality is significantly influenced by these parameters. We identified two distinct zones on the cut surface: one with favorable roughness and another with less favorable roughness. Overall, increasing laser beam power led to improved surface quality, while increasing the feed rate resulted in a degradation of the surface. By analyzing the experimental data, we identified an optimal parameter combination for achieving high surface quality. These discoveries have practical applications in business and help to a theoretical knowledge of the laser cutting process.